Mechanically stable thermally cross linked poly(acrylic acid)/reduced graphene oxide aerogels - Ha, Heonjoo; Shanmuganathan, Kadhiravan; Ellison, Christopher J. (ACS Applied Materials & Interfaces, 2015)
Graphene oxide (GO) aerogels, high porosity (>99%) low density (similar to 3-10 mg cm(-3)) porous materials with GO pore walls, are particularly attractive due to their lightweight, high surface area, and potential use in environmental remediation, superhydrophobic and superoleophilic materials, energy storage, etc. However, pure GO aerogels are generally weak and delicate which complicates their handling and potentially limits their commercial implementation. The focus of this work Vas to synthesize highly elastic, mechanically stable aerogels that are robust and easy to handle without substantially sacrificing their high porosity or low density. To overcome this challenge, a small amount of readily available and, thermally cross-linkable poly(acrylic acid) (PAA) was intermixed with GO to enhance the mechanical integrity Of the aerogel without disrupting other desirable characteristic properties. This method is a simple straightforward procedure that does not include multistep or complicated chemical reactions, and it produces aerogels with mass densities of about 4-6 mg cm(-3) and >99.6% porosity-that can reversibly support up to 10 000 times their weight with full recovery of their original volume. Finally; pressure sensing capabilities were demonstrated and their oil absorption capacities were measured to be around 120 g oil per g aerogel(-1) which highlights their potential Use in practical applications.
Keywords: aerogels; environmental remediation; graphene; Nanocomposites; poly(acrylic acid)